2021
DOI: 10.1051/0004-6361/201936231
|View full text |Cite
|
Sign up to set email alerts
|

ALMA small-scale features in the quiet Sun and active regions

Abstract: Aims. The main aim of the present analysis is to decipher (i) the small-scale bright features in solar images of the quiet Sun and active regions obtained with the Atacama Large Millimeter/submillimeter Array (ALMA) and (ii) the ALMA correspondence of various known chromospheric structures visible in the Hα images of the Sun. Methods. Small-scale ALMA bright features in the quiet Sun region were analyzed using single-dish ALMA observations (1.21 mm, 248 GHz) and in an active region using interferometric ALMA m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 40 publications
(49 reference statements)
1
12
0
Order By: Relevance
“…Surprisingly, no clear cospatial counterpart of the mm umbral enhancement was found in the AIA 1700A, 304A, or 171A channels, although they showed generally similar large-scale structure of the AR plage as in the mm image. Brajša et al (2021) analyzed the same active region mosaic and confirmed the umbral brightening. These authors also identified several correspondences between temperature enhancements in the region surrounding the sunspot and chromospheric fibrils and coronal bright points seen in several AIA/SDO channels (Figure 2).…”
Section: Thermal Structurementioning
confidence: 63%
See 1 more Smart Citation
“…Surprisingly, no clear cospatial counterpart of the mm umbral enhancement was found in the AIA 1700A, 304A, or 171A channels, although they showed generally similar large-scale structure of the AR plage as in the mm image. Brajša et al (2021) analyzed the same active region mosaic and confirmed the umbral brightening. These authors also identified several correspondences between temperature enhancements in the region surrounding the sunspot and chromospheric fibrils and coronal bright points seen in several AIA/SDO channels (Figure 2).…”
Section: Thermal Structurementioning
confidence: 63%
“…Mapping of the Sun with spatial resolution of order of arcseconds has revealed the fine structure of the solar radio emission from ARs. With ALMA it became possible to distinguish and describe sunspot umbra and penumbra in the mm images (Iwai et al, 2017;Loukitcheva et al, 2017), to study signatures of the three-minute oscillations and wave propagation in the mm brightness of sunspot umbra (Chai et al, 2022a), to detect oscillations of mm brightness in small bright features in a plage (Guevara Gómez et al, 2021), to study spatial association of the observed oscillations through the atmosphere mapped by the different passbands (Narang et al, 2022), and evaluate the contribution from detected high-frequency acoustic waves to the chromospheric heating in plages (Molnar et al, 2021), to explore AR small-scale transient brightenings as signatures of heating linked to magnetic reconnection events (da Silva Santos et al, 2020b) and to provide further evidence for heating in the upper chromosphere through current dissipation (da Silva Santos et al, 2022a), to image a solar active region filament at sub-arcsecond resolution with the Interface Region Imaging Spectrograph (IRIS, De Pontieu et al, 2014) and ALMA (da Silva Santos et al, 2022b), to explore the structure and the dynamics of chromospheric plages, namely, of fibrils (Chintzoglou et al, 2021a) and jet-like features (Type II spicules) (Chintzoglou et al, 2021b), to perform quantitative comparison between the mm continuum brightness and the chromospheric diagnostics from observations, e.g., with Hα (Molnar et al, 2019), and Mg II line Bastian et al, 2018;Jafarzadeh et al, 2019), to constrain the thermodynamical properties of the plage atmosphere using ALMA and IRIS data from a NLTE inversion code (da Silva Santos et al, 2020a), and finally, to identify small-scale bright features in the ALMA images and study their relation to the chromospheric structures seen in the EUV, UV and Hα images (Brajša et al, 2018(Brajša et al, , 2021, and to employ ALMA measurements in a data-constrained model of the sunspot's atmosphere (de Oliveira e Silva et al, 2022). Below we provide more details about these observational results.…”
mentioning
confidence: 99%
“…A good dark-dark correspondence (sunspot and small filaments) and bright-bright correspondence (plages) between the two images was indeed found by Brajša et al (2021). However, the relationship between Hα core and highresolution ALMA images in the millimeter wavelength range is more complicated, since these authors found examples of both types of behavior, correlation and anticorrelation.…”
Section: Morphology and Comparison With Other Wavelength Rangesmentioning
confidence: 79%
“…Moreover, all ALMA 1.21 mm bright points show a well-defined relationship with magnetic structures (100% correspondence), mostly with small-scale bipolar magnetic regions and in some cases with small unipolar magnetic regions. Brajša et al (2021) investigated small-scale ALMA bright features in the quiet Sun region using a full-disk solar image produced with single-dish ALMA measurements (1.21 mm, 248 GHz) performed on 18 December 2015. The selected quiet Sun region was compared with the EUV and soft X-ray images and with the magnetograms (Figure 7).…”
Section: Morphology and Comparison With Other Wavelength Rangesmentioning
confidence: 99%
“…Period UT Project code Freq. N GHz 2017- 04-23 14:06 -16:30 2016.1.01129.S 230 9 2017-04-26 14:17 -16:19 2016.1.00070.S 107 11 2018-04-03 13:47 -17:39 2017.1.00072.S 95 23 2018-04-19 15:26 -17:47 2017.1.01138.S 95 14 2018-12-15 13:08 -15:12 2018.1.01879.S 95 10 For this reason, solar ALMA observations in the past have focused on stationary phenomena such as radius, center-to-limb and center -to-pole brightnening measurements (Alissandrakis et al 2017;Selhorst et al 2019;Sudar et al 2019a,b;Menezes et al 2021Menezes et al , 2022, identification and analysis of various stationary structures in full disk (Brajša et al 2018;Skokić et al 2020) and interferometric ALMA images (Iwai et al 2017;Bastian et al 2017;Nindos et al 2018;Jafarzadeh et al 2019;Rodger et al 2019;Loukitcheva et al 2019;Molnar et al 2019;Shimojo et al 2020;Wedemeyer et al 2020;Brajša et al 2020Brajša et al , 2021.…”
Section: Datementioning
confidence: 99%